Архітектура тимчасового житла на прикладі фестивалю BURNING MAN - Грицюк, Леся; Босюк, Крістіна; Hrytsyuk, Lesia; Bosyuk, Kristina (Видавництво Львівської політехніки, 2020)
Розглянуто еволюцію видів тимчасового житла на прикладі арт-фестивалю Burning Man у США. У світі щороку відбувається багато культурних, мистецьких заходів, які на довший чи коротший термін приваблюють велику кількість людей. Незважаючи на тимчасовий характер таких подій, необхідне забезпечення багатьох потреб гостей робить фестиваль відповідною лабораторією для вивчення експлуатаційних функцій тимчасового житла з можливістю експериментувати з новими стійкими рішеннями в прискореному контексті, що може генерувати нові уявлення про архітектуру тимчасового житла.

The evolution of temporary housing types is reviewed on the example of the Burning Man Art Festival in the USA. Many annual cultural, artistic events in the world attract a large number of people for a longer or shorter period. Despite the temporary nature of those events, there is a necessity in providing lots of needs of guests. It makes the festival an appropriate laboratory for exploring the operational functions of temporary housing, with the opportunity to experiment with new sustainable solutions on an expedited basis that may generate new insights on temporary housing architecture. This article describes several types of Burning Man’s temporary housing units, causes and factors that made them start changing, who invented those units. By reading this article we can understand which type is better for special conditions like the climate of the Nevada desert. The purpose of the article is to research the evolution of the temporary housing and to determine the most relevant types of living units for extreme circumstances on the example of the festival in the Nevada desert, to explore their differences, effectiveness and the relevance of using them in other fields (emergency shelters, military representations abroad, temporary housing/offices for building experts, temporary resettlement, etc). Different forms and configurations, materials, weight, difficulties in transportation and complexity of setting up. The subject of temporary housing is important to learn and research. It is open for new inventors and their ambitious engineering solutions. It is urgent both for special events such as seasonal festivals in the highly unstable weather conditions and for overcoming consequences of natural and technological disasters. The temporary housing is an alive and developing issue.
Temporary housing architecture on example of BURNING MAN festival
Keywords: тимчасове житло; події; інновації; фестиваль; екстремальні умови; temporary housing; events; innovations; festival; extreme conditions; 728.222